Polska powieść uniwersytecka - Sidowska, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article presents the genre of campus novel, referring to two examples from contemporary Polish literature: “Sto dni bez słońca” by Wit Szostak and “Na krótko” by Inga Iwasiów. In both works you can find the most important characteristics of the genre: defined scenery, narrative schemes, chronotopos, gallery of typical characters, but only Szostak follows the typical satirical convention. On the other hand the genre-pattern has been enriched by new elements, e.g. a feminine perspective of description by Iwasiów. Both novels have a common aspect, which is the introduction of science fiction elements, and reveal the most current problems of the university, especially the humanities, at the beginning and in the subsequent decades of the 21st century. Noteworthy is also the creation of characters, which is the result of a conscious play with the stereotype of the scientist.